Probing the Sources of the Scroll of Antiochus: The Case for the Syriac Version of 1 Maccabees - Stadel, Christian (2025)
The Scroll of Antiochus purports to be a contemporaneous account of the revolt of the Hasmonaeans and the miracle of the oil. It is written in a kind of literary Aramaic that imitates the biblical and targumic Aramaic dialects and was probably composed in gaonic Babylonia as an etiology for the festival of Hanukkah. Since the text relates details of the revolt that have not been preserved in rabbinic writings, it is usually assumed that its author relied on Greek sources such as 1 Maccabees or Josephus’s writings. But knowledge of Greek was not common among Babylonian Jews. Based on a lexical correspondence in the wording of one section of the scroll and in the Syriac translation of 1 Maccabees, I argue that the author of the Scroll of Antiochus relied on this latter version for the historical details of the revolt. Syriac is a Christian Aramaic dialect from Mesopotamia that resembles Jewish Babylonian Aramaic. Recent research has found evidence for knowledge of Syriac in Jewish circles and for the adaption of Syriac texts into square script, which provides a fitting background for my hypothesis. The findings contribute to a refined picture of the composition of the Scroll of Antiochus.
Keywords: Judeo-Syriac; Babylonia; Jewish-Christian interaction; Syriac; 1 Maccabees; Scroll of Antiochus